Impact and Risk Management Strategies on East Surabaya Hospital Construction Projects: A Technical, Time, Cost, and Environmental Approach - Mochammad Djatmiko; Andi Patriadi; Sajiyo Sajiyo (Journal of Social Science, 2025)
This study examines the impact and risk management strategies in the construction of East Surabaya Hospital, focusing on technical, time, cost, and environmental aspects. Using a comprehensive mixed-method approach, the research integrates SWOT analysis and Failure Mode and Effects Analysis (FMEA) with Environmental Impact Assessment (AMDAL) documentation to ensure a thorough evaluation of risks. Extensive data collection was conducted through stakeholder interviews, structured questionnaires, and field observations to identify significant risks across multiple dimensions. The findings reveal that environmental risks constitute 45% of total project risks, stemming from air and noise pollution and community disruptions, while technical risks, including equipment failures and material delays, contribute 35%. Temporal and financial risks, though less dominant, showed a cascading effect on overall project efficiency. Implemented risk mitigation strategies, such as preventive equipment maintenance, trusted supplier contracts, dust control measures, and transparent community engagement, successfully reduced technical risks by 25% and environmental impacts by 30%. Statistical analysis demonstrated a strong positive correlation between risk mitigation efforts and project success, with a p-value of 0.02, highlighting the effectiveness of these measures. The study underscores the importance of integrating environmental considerations with technical, temporal, and financial risk management strategies. It provides valuable insights for developing adaptive and sustainable risk management frameworks for urban hospital construction projects, ensuring project success while fostering environmental sustainability and community acceptance.